LABOR MARKET INTEGRATION OF REFUGEES IN GERMANY: EMPLOYERS’ EXPERIENCES AND CONSEQUENCES (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
In the light of a recent surge of refugee migration to Germany, labor market integration as well as employers’ experiences and consequences are key determinants of immigration’s macroeconomic welfare impacts. Our contribution aims at analyzing recent empirical evidence of employers’ expectations, obstacles, consequences and benefits as well as strategies to strengthen refugees’ labor market inclusion. To achieve these goals, we first sketch potential negative and positive short- and long-run macroeconomic immigration effects on host countries like Germany and the decisive role of refugees’ labor market integration in this respect. Then, employers’ expectations and obstacles of refugee employment are discussed. Furthermore, employers’ overall experiences, their engagement in hiring refugees and the resulting employment status of refugees in Germany are reconsidered. Based on secondary quantitative research and qualitative findings, we argue that refugees’ labor market situation may change in the future, particularly as female refugees frequently adopt considerably higher employment aspirations in Germany compared to their countries of origin, in which they have often been restrained by diverse obstacles. We finally analyze and discuss major ways to improve refugees’ labor market perspectives in general, and for female refugees specifically.